A guide to standardized methods of analysis for soil, water, plant, and fertilizer resources for data documentation and sharing in Ethiopia - Wogi, Lemma; Dechassa, Nigussie; Haileselassie, Bereket; Mekuria, Fikre; Abebe, Ayele; Tamene, Lulseged D. (International Center for Tropical Agriculture, 2021)
This guide is intended to serve as standard reference source for collecting, analyzing, interpreting, documenting, and sharing data on soil, plant, water, and fertilizer resources. It has been prepared by considering and adopting limited numbers of simple but effective methods and procedures for collecting, analyzing, documenting, and sharing data on soil, plant, water, and fertilizer resources in Ethiopia and has been specifically developed by reviewing standard methods and procedures of analyzing soil, plant, water, and fertilizer from the literature (Sertsu and Bekele, 2000; Bashour and Sayegh, 2007; FAO, 2008; Singh et al., 2010; Benton Jones, 2012; Estefan et al., 2013). The Guide is also intended to enable national collation, verification, and publication of hitherto collected and future data on soil, plant, water, and fertilizers that can be acquired from research institutes, universities, colleges, CGIAR Research Centers, and researchers.